Analisis Faktor yang Mempengaruhi Tingginya Turnover Karyawan pada Fuji Pre-School Jakarta - Shahab, Nur Dina; Aini Juleha, Nur (Cv. Syntax Corporation Indonesia, 2020)
This research aims to identify of factor that affecting the high employee turnover in Fuji Pre-School. This researched located in Fuji Pre-School at Antene 3 No. 10, Gandaria Utara, Jakarta Selatan. Respondent of the research is 48 respondent which is ex-employees and employees. The research used quantitatived explanation method using the multiple analysis of linear regression, analysis of correlation and using SPSS software. The high of employee turnover created a negative image on school. Negative image affected to reduction of the new students and reduce works spirits of employee. The high of employee turnover is also bothering some school activities become a trouble. The first hypothesis examines whether work satisfaction variable affecting to the high employee turnover. The second hypothesis examines whether organizational commitment affecting the high employee turnover. The third hypothesis examines whether work satisfaction and organizational commitment affecting simultaneously with the high employee turnover. The result is highlight significant relation between works satisfaction and organizational commitment with employee turnover. Both works satisfaction and organizational commitment has a negatively related to the employee turnover. Based on the results can simply that Fuji Pre-School must recovered the management and payroll system that will makes work condition more conducive and kinship. And finally can push the high employee turnover in Fuji Pre-School.